ANALYZING THE EFFECT OF ROAD PERFORMANCE INDICATORS ON PENALTIES FOR LATE FULFILLMENT IN ROAD SERVICE LEVELS - Sita, Tisara; Mulyono, Agus Taufik; Utomo, Suryo Hapsoro Tri (Journal of Applied Engineering Science, 2022)
The long segment policy for national road preservation comprising routine maintenance work, both road routine and condition routine maintenance, preventive maintenance, and holding with widening, rehabilitation, and reconstruction of several road sections into a single contract had been implemented in Indonesia since 2016. Reliable road performance indicators including road pavement, road shoulders, drainage, road equipment, road complementary buildings, and clearances have an impact on-road performance. Therefore, an analysis must be carried out to obtain indicators for each road performance influencing Penalties for Late Fulfillment in Road Service Levels (PLRSL) charged to contractors if they could not meet the road performance indicators based on the specified repair response time. This study aims to improve the road service level through the compliance of road performance indicators on the success of sustainable construction projects. The Structural Equation Modeling (SEM) analysis results indicated that the road performance indicator in the road preservation program had a significant effect of 77.0% on the determination of PLRSL. In addition, road pavement, drainage, road shoulder, clearance, complementary buildings, and road equipment contributed statistically significant effect on the road performance indicator with values of 88.0%, 81.4%, 80.9%, 79.1%, 78.1%, and 51.3%, respectively. These results should be a concern for contractors and the government. With a clear understanding of the significant indicators in the context of the road maintenance project, these findings could potentially contribute to the development of comprehensive pavement handling on road maintenance programs related to the quality performance of the construction projects.